Employee Performance with Employee Engagement as an Intervening Variable: Individual Career Development and Competency - Mulyani, Sitti Rizki; Trinanda, Zikri; Yeni, Fitri; Afuan, M.; Nurhamzah (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2024)
By using employee engagement as an intervening variable, this research aims to find out how individual career development and competency impact the performance of Bank Nagari Pangkalan employees. The analysis methodology is Structural Equation Modeling (SEM), which uses Partial Least Square (PLS), and distributed questionnaires to 74 respondents. The research results show that individual career development and competency have a significant positive effect on employee engagement, individual career development has a significant positive effect on employee performance, while employee engagement doesn’t have a significant effect on bank employee performance. Employee engagement doesn’t mediate the relationship between individual career development and competency on the performance of Bank Nagari Pangkalan employees.